A chamada pública de ATER indígena e a perspectiva de construção do “etnodesenvolvimento”: análise de uma experiência no Rio Grande do Sul - Brutti, Cleuza Noal (2019)
The research work contextualizes the secular trajectory of the assistance provided by the Brazilian national state to indigenous peoples. Through semi-structured interviews, participant observation and bibliographic and documentary research it is sought to analyze the meanings of the experience of operationalizing a public policy. It emphasizes public policies of the 2000s, which propose a break with assistance and social and productive exclusion. It draws attention to the pioneering Public Call of Indigenous ATER and the Program to Promote Rural Productive Activities, under the Brazil Without Misery Plan (PBSM). It describes how these public policies were implemented in the largest indigenous land in the contingent of Rio Grande do Sul State, the Guarita Indigenous Land. It indicates Innovations, produced by public policy, with no two-year progress, during which time EMATER / RS-ASCAR played a leading role in providing assistance services to the Kaingang and Guarani. It explores meanings produced by the public call and Fomento and, in the light of Roberto Cardoso de Oliveira's notions of participation, and Pierre Bourdieu's cultural capital and school capital, discusses and proposes justifications for the impossibility of realizing the systematized foundations of ethnodevelopment, by Rodolfo Stavenhagen.